Epstein-Barr virus-related lymphoproliferative disorders of the skin - Gerardo Ferrara; Alberto Gualandi (PAGEPress Publications, 2024)
Epstein Barr Virus (EBV) is associated both solid (nasopharyngeal carcinoma, non-nasopharyngeal lymphoepithelioma- like carcinoma, gastric carcinoma, leiomyosarcoma) and hematolymphoid malignancies, some of the latter, however, spanning over a spectrum ranging from reactive and self-limiting to severe and life-threatening conditions. This review will focus on the disorder most commonly involving the skin, namely: EBVpositive mucocutaneous ulcer; lymphomatoid granulomatosis; EBV-positive diffuse large B cell lymphoma; plasmablastic lymphoma; post-transplant lymphoproliferative disorder; extranodal NK/T cell lymphoma, nasal type; angoimmunoblastic T cell lymphoma; severe mosquito bite allergy; hydroa vacciniformelike lymphoproliferative disorder. Given the uncommon occurrence of all these infiltrates in the skin, multidisciplinary approach, as well as referral to tertiary care centers are always advisable.